Physiological intron retaining transcripts in the cytoplasm abound during human motor neurogenesis - Petrić Howe, Marija; Crerar, Hamish; Neeves, Jacob; Harley, Jasmine; Tyzack, Giulia E.; Klein, Pierre; Ramos, Andres; Patani, Rickie; Luisier, Raphaëlle (Genome Research, 2022)
Intron retention (IR) is now recognized as a dominant splicing event during motor neuron (MN) development; however, the role and regulation of intron-retaining transcripts (IRTs) localized to the cytoplasm remain particularly understudied. Here we show that IR is a physiological process that is spatiotemporally regulated during MN lineage restriction and that IRTs in the cytoplasm are detected in as many as 13% (n = 2297) of the genes expressed during this process. We identify a major class of cytoplasmic IRTs that are not associated with reduced expression of their own genes but instead show a high capacity for RNA-binding protein and miRNA occupancy. Finally, we show that ALS-causing VCP mutations lead to a selective increase in cytoplasmic abundance of this particular class of IRTs, which in turn temporally coincides with an increase in the nuclear expression level of predicted miRNA target genes. Altogether, our study identifies a previously unrecognized class of cytoplasmic intronic sequences with potential regulatory function beyond gene expression.
10.1101/gr.276898.122